Identifikasi Genetik Ikan Nilem dengan Pendekatan DNA Barcoding - Dailami, Muhammad; Yuniarti, Ating; Widodo, Maheno Sri; Pratama, Rakhmad Ndaru; Ariyani, Destia Fitri; Siahaan, Marthin Daniel Theo Gratia; Maulana, Antajala Rian; Ramadhan, Surya Dewa; Putri, Radwa Fathin H; Nurcahyani, Shinta Eka; Milansari, Sindi; Mayor, Corazon Ell Merilia Papuani (Journal of Tropical Diversity, 2025)
Nilem fish (Osteochilus vittatus) is a species of freshwater fish from the Cyprinidae family which has ecological and economic importance in Indonesia, with its natural habitat in rivers, swamps and stagnant waters. Accurate species identification is very important in biological research and fisheries resource management, but morphological identification methods have several limitations. DNA barcoding is a revolutionary molecular technique that uses short DNA sequences to identify and differentiate species with high accuracy. The use of DNA barcoding in identifying freshwater fish in Indonesia has shown significant development, including in a comprehensive study documenting 1,172 native freshwater fish species. The research "Genetic Identification of Nilem Fish using the DNA Barcoding Approach" aims to characterize the genetics of nilem fish, compare the genetic profiles of various populations, and evaluate the effectiveness of DNA barcoding in distinguishing nilem fish from other Osteochilus species, with the hope of contributing to fish conservation and sustainable management efforts nilem in Indonesia. The DNA sequencing results obtained a sequence with a length of 619 base pairs with the composition of Nucleotides A (27.2%), G (17.6%), C (26.4%), T (28.8%). The BLAST results with the NCBI database showed a similarity of 99.84% with the O. vittatus sequence and 99.83% with O. hasseltii. Both species are synonyms with the official name O. vittatus. Phylogenetic analysis is also in line with the BLAST results which show that the sample sequence is in the same clade as the O. vittatus and O. hasseltii sequences. Identification with molecular markers of the COI gene was successfully used in determining the species of the Nilem fish (O. vittatus).